GC-MS Analysis of Vitis vinifera var. Sultana (White Grapes) and Vitis vinifera var. Cabernet Sauvigno(Black Grapes) fermented Juices and Their Role of Controlling Dieback Disease in Neem Trees at Nizamabad District Telangana, India - K. Chaithanya Shanthi; M. Mamatha (The Bioscan, 2025)
This study investigates the bioactive compounds present in fermented white and black grape juices (FFJ) and their potential antifungal activity against Phomopsis azadirachtae, the causative agent of dieback disease in Neem trees. Gas chromatography-mass spectrometry (GC-MS) analysis revealed a diverse array of bioactive compounds in both fermented juices, including antioxidants, antimicrobial agents, and anti-inflammatory compounds. The antifungal efficacy of these fermented juices was evaluated using the poisoned food technique, demonstrating significant inhibition of fungal growth. The findings suggest that fermented grape juices could serve as a sustainable and eco-friendly alternative to chemical fungicides for managing dieback disease in Neem trees.